2020
DOI: 10.1038/s41598-020-61719-3
|View full text |Cite
|
Sign up to set email alerts
|

The influence of transmitted and non-transmitted parental BMI-associated alleles on the risk of overweight in childhood

Abstract: Overweight in children is strongly associated with parental body mass index (BMI) and overweight. We assessed parental transmitted and non-transmitted genetic contributions to overweight in children from the Danish National Birth Cohort by constructing genetic risk scores (GRSs) from 941 common genetic variants associated with adult BMI and estimating associations of transmitted maternal/ paternal and non-transmitted maternal GRS with child overweight. Maternal and paternal BMI (standard deviation (SD) units) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 44 publications
1
11
0
1
Order By: Relevance
“…This suggests the absence of dynastic effects by which the offspring phenotype is influenced indirectly by the noninherited alleles affecting parents (i.e., nurturing effects). This is in line with Scnurr et al, which showed maternal nontransmitted genetic risk score (GRS) to not be associated with offspring overweight (41). In disagreement with our results, Kong et al showed that the nontransmitted alleles from parents influence offspring by 29.9% (37), although their study design and trait (education attainment) in focus were different from ours.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…This suggests the absence of dynastic effects by which the offspring phenotype is influenced indirectly by the noninherited alleles affecting parents (i.e., nurturing effects). This is in line with Scnurr et al, which showed maternal nontransmitted genetic risk score (GRS) to not be associated with offspring overweight (41). In disagreement with our results, Kong et al showed that the nontransmitted alleles from parents influence offspring by 29.9% (37), although their study design and trait (education attainment) in focus were different from ours.…”
Section: Discussionsupporting
confidence: 87%
“…As part of understanding the inheritance of obesity, the effect of nontransmitted alleles from parents that may indirectly affect the genetic variance in a family setting should be considered (37,40,41). This feature, defined as “genetic nurture,” takes into account that nontransmitted obesity‐susceptibility alleles in parents affecting parental obesogenic traits will further influence children's obesity vulnerability indirectly through their home environment (37).…”
Section: Discussionmentioning
confidence: 99%
“…Such associations are due to indirect effects of maternal genotype on offspring adiposity, mediated via the offspring's pre or postnatal environment (67) (also known as genetic nurture (68), dynastic effects (69) and social genetic effects (70)). These observed maternal genetic effects merit further investigation in other datasets, particularly as previous studies have not found evidence for parental genetic effects on BMI in childhood (71) or adulthood (68).…”
Section: Discussionmentioning
confidence: 74%
“…The interaction estimates in boys attenuated most upon adjustment for parental BMI values. This is unsurprising given the known strong associations between parental and offspring BMI [7,42], part of which are genetic and part of which are due to shared environmental factors [43,44]. Shared environmental factors are likely to promote rapid infant weight gain and low MVPA, perhaps in addition to genetic effects related to parental BMI [45,46].…”
Section: Discussionmentioning
confidence: 99%